Peran Pendidikan Agama Islam Dalam Menanggulangi Krisis Karakter Pada Remaja di Smk Muhammadiyah 2 Boja - Arumpurwasih; Hadi, Syaiful (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The crisis of character among adolescents in secondary schools has become an increasingly complex social issue, influenced by many factors such as the environment, school, and family. In this context, Islamic religious education plays a vital role in shaping the character of adolescents through the moral and ethical values taught in religion. The aim of this study is to analyze the role of Islamic religious education in addressing the character crisis among adolescents in secondary schools. This study uses a qualitative approach with a case study method, involving observation, interviews, and documentation as data collection tools. The results of the study show that Islamic religious education in secondary schools has a positive impact on character development, particularly in terms of honesty, discipline, and responsibility. Furthermore, the application of Islamic values in students' daily lives helps reduce negative behaviors commonly exhibited during adolescence. The responsibility for character development does not lie solely with the Islamic religious education teacher but also involves all parties, including other subject teachers, counseling teachers, and educational staff. Based on these findings, it is recommended that Islamic religious education be strengthened and integrated into various aspects of students' lives in school to address the ongoing character crisis.